Maternal vitamin deficiency mimicking multiple acyl-CoA dehydrogenase deficiency on newborn screening - Gramer, Gwendolyn; Hoffmann, Georg F.; Hennermann, Julia B. (Molecular genetics and metabolism reports, 2021)
Background - In infancy multiple acyl-CoA dehydrogenase deficiency (MADD) is commonly a severe inherited metabolic disease caused by genetic defects in electron transfer flavoprotein (ETF) or ETF ubiquinone oxidoreductase. Both enzymes require flavin adenine dinucleotide (FAD) as a cofactor. Riboflavin (vitamin B2) is a precursor in the synthesis of FAD. MADD can be detected by newborn screening (NBS) based on elevation of multiple acylcarnitines. - Methods - We present the results of two children whose NBS results and subsequent confirmatory testing resulted in a suspected diagnosis of MADD. In parallel in both children vitamin B12 deficiency was detected. - Results - Biochemical profiles normalized rapidly in both children under supplementation with riboflavin. After extensive work-up of both cases including molecular genetic studies there was no indication of MADD. Vitamin B12 deficiency in both children was caused by maternal vitamin B12 deficiency and was rapidly corrected by oral supplementation with vitamin B12 or (partial) formula feeding. As both vitamin B12 and riboflavin have similar food sources we postulate that in these cases positive NBS for MADD was caused by combined maternal vitamin B deficiencies. - Conclusion - The differential diagnosis of maternally caused vitamin B deficiencies should be considered in children with abnormal NBS results for MADD, especially in the presence of normal molecular genetic analysis or in case of associated findings of other maternal vitamin B deficiencies like vitamin B12 or folic acid deficiency.
Gesehen am 06.08.2021